New Composite Material of Thermoset Base Reinforced by Micro-hyper-woven Fiber Resistance for Petroleum Derivatives - Nagham H. Abood (Journal of Global Pharma Technology, 2019)
A new composite of polyester reinforced by micro-hyper-woven glass and carbon fibers has been prepared to obtain unique mechanical and thermal properties and physicochemical activity such as high specific strength, stiffness and corrosive resistance to different hydrocarbon derivatives. In this experimental work, an attempt has been made to test the aging of new hyper composites in terms of their thermo mechanical properties by changing the weight percent, Cw/gw, of the additive woven mixed fiber in the range of (1, 2, 3). This new composite is fabricated by manually layering the base polyester matrix and reinforced hyper woven fibers 200/20 (gm/gm) from the base matrix, and a hardener is applied for each cast with 1 gm of micro-zirconium. Different aging results of the thermo mechanical properties (thermal conductivity, thermal expansion, impact strength, flexural strength, tensile strength, elongation, hardness, and compression resistance) are obtained according to the American Society for Testing and Materials (ASTM) standards. The results for these aging thermo mechanical properties after one month show that the specimens reinforced by hyper woven gw/Cw with three percentage mixing ratios (1, 2, 3 wt.%) have excellent aging thermo mechanical properties. Keywords: Hyper woven fiber, Polyester composite, Aging characteristic properties.